Oil well cement fluid loss agent without thickening time upside down and preparation method thereof
The oil well cement water loss reducing agent prepared through copolymerization reaction uses methyl power supply effect and weak polar bond technology to solve the problem of thickening time inverted by the existing water loss reducing agent under high temperature conditions, and realizes the temperature resistance, salt resistance and stability of the water loss reducing agent, ensuring the safety and efficiency of the cementing project.
Patent Information
- Application Number
- CN202411904706.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-23
AI Technical Summary
Existing oil well cement loss-reducing agents are prone to invert thickening time under high temperature and high alkaline conditions, resulting in the cement slurry solidification early, causing engineering accidents and economic losses.
By copolymerizing four monomers, N,N-dimethacrylamide, 3-allyloxy-2-hydroxy-1-1 propansulfonate, vinylpyrrolidone, and sodium methylallylsulfonate, a new oil well cement water loss reduction agent was prepared. The hydrolysis of the amide group was weakened by the power supply effect of the methyl group, and the anti-temperature and salt-resistant sulfonic acid group was connected with weak polar bonds, solving the stability of the water loss reduction agent under high temperature conditions.
The prepared water-reducing agent has no thickening time inverted when the temperature range of 90℃~120℃, eliminating major engineering safety risks in cementing projects, improving the temperature resistance, salt resistance and stability of cement slurry, and ensuring the controllability and safety of cement slurry under high temperature conditions.
Smart Images

Figure CN119708335A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of oil drilling, in particular to an oil well cement fluid loss reducing agent with no inverted thickening time and a preparation method thereof. Background Art
[0002] The process of injecting cement slurry into the annular space between the wellbore formed by drilling and the casing inserted, and solidifying the cement slurry to isolate the formation fluid is called cementing. Cementing provides basic conditions for subsequent oil and gas production, oil and gas well production increase, production layer transformation, well repair and other projects, and is a key link in the construction of oil and gas wells. During the cementing process of oil fields, when the cement slurry flows through the permeable formation, under the action of pressure difference, the liquid phase in the cement slurry will permeate into the formation. This phenomenon is called water loss of cement slurry. Water loss pollutes the oil and gas layer, reduces the production of oil and gas wells, and affects the consistency of downhole cement slurry performance with the designed performance. Usually, oil well cement fluid loss reducer is added to the cementing cement slurry system to control water loss. At present, more than 90% of the fluid loss reducers actually used in oil and gas well cementing projects are binary, ternary, and multi-polymers of acrylamide (AM), 2-acrylamido-2-dimethylpropane sulfonate (AMPS) and some other monomers, among which AM and AMPS account for 70% to 80% of the polymer.
[0003] In cementing engineering, cement slurry is required to be in a pumpable state during the construction process, that is, the cement slurry cannot solidify and the cement slurry consistency must be kept below 30Bc. The thickening time is the cement slurry solidification time measured under simulated downhole engineering conditions, which is the time to ensure the safe construction of the project; premature thickening (solidification) of cement slurry will cause serious engineering accidents and huge economic losses. Generally, the higher the temperature, the faster the cement hydration speed and the shorter the thickening time; the lower the temperature, the slower the cement hydration speed and the longer the thickening time; if the higher the temperature, the longer the thickening time, and the lower the temperature, the shorter the thickening time, it is called the "inverted" thickening time of cement slurry in engineering. With the rapid development of drilling and cementing technology, the cementing temperature is getting higher and higher, the bottom of the oil layer can reach above 230℃, and the corresponding circulation temperature (thickening time measurement temperature) reaches above 180℃; the one-time sealing section is getting longer and longer, up to more than 5000m; the temperature difference is getting larger and larger, up to more than 80℃. The thickening time of cement slurry is designed and measured based on the bottom hole circulation temperature. If the thickening time of cement slurry is inverted, when the cement slurry is in the low temperature stage during the lowering process or the returning process, it will solidify prematurely due to the inverted thickening time (i.e., short curing time), which will cause major engineering accidents such as "stuffing sausages" and "planting flagpoles", that is, the inverted thickening time has huge engineering risks. The inverted thickening time is mainly due to the hydrolysis of the amide groups (AM and AMPS both contain amide groups) in the copolymer of AM / AMPS copolymer admixtures under high temperature and high alkalinity conditions to produce too many carboxyl groups with retarding ability; at the same time, the oil well cement fluid loss reducer produces high temperature chain scission, functional group degradation, high temperature desorption, high temperature dehydration and other problems, which will lead to the cement slurry system losing water and losing control, reducing gravity stability (cement slurry sedimentation), and the occurrence of "heart", "bulging", "stepping", "super retarding" and other undesirable phenomena in the cement slurry thickening process. Since the temperature at which amide groups undergo a large amount of hydrolysis is between 90 and 120°C, the inverted temperature range is generally in the cementing process across the 90°C to 120°C temperature zone; and a large amount of technical casing and oil layer casing cementing must cross this temperature zone. Therefore, solving the inverted thickening time of fluid loss reducers is a technical problem that must be solved to prevent major risks in cementing projects and improve cementing quality. Summary of the invention
[0004] In order to solve the problem of inverted thickening time of current fluid loss reducers, the present invention provides an oil well cement fluid loss reducer without inverted thickening time and a preparation method thereof.
[0005] The oil well cement fluid loss reducer with no inverted thickening time provided by the present invention has the following preparation method:
[0006] S1. Add four raw material monomers, namely, N,N-dimethylacrylamide, sodium 3-allyloxy-2-hydroxy-1-1 propanesulfonate, vinyl pyrrolidone and sodium methyl allyl sulfonate, into water, stir and dissolve to obtain a reaction solution; the mass ratio of the four monomers, namely, N,N-dimethylacrylamide, sodium 3-allyloxy-2-hydroxy-1-1 propanesulfonate, vinyl pyrrolidone and sodium methyl allyl sulfonate, is (44-46):(18-21):(6-9):(4-7).
[0007] S2. Raise the temperature of the reaction solution to 60°C ± 2°C, add the initiator solution dropwise within 3 to 5 minutes, and keep the temperature at 80 to 85°C for 6 hours; during the reaction, the reaction temperature is controlled not to exceed 85°C by circulating cooling water.
[0008] S3. After the reaction time reaches 6 hours, add the terminator thiourea solution to terminate the reaction; and start the circulating cooling water, and cool down to below 40°C while stirring. The obtained solution is the fluid loss reducer.
[0009] In the entire reaction system, the mass ratio of water to the total mass of the four monomers is 74:16. The water includes the water used in step S1 and the total amount of water in the initiator solution and the thiourea solution.
[0010] Preferably, the initiator is sodium persulfate, and the amount of the initiator used is 2.0% of the total mass of the four monomers, and an initiator solution with a mass percentage concentration of 35% is prepared by dissolving in water.
[0011] Preferably, the thiourea solution is a solution formed by dissolving thiourea in water with a mass percentage concentration of 10%, and the amount of thiourea used is 0.1% of the total mass of the four monomers.
[0012] The reaction principle formula for preparing the oil well cement fluid loss reducer without inverted thickening time of the present invention is as follows:
[0013]
[0014] Compared with the prior art, the present invention is beneficial in that:
[0015] (1) The present invention replaces two hydrogen atoms on the amidoamine with methyl groups having a power supply effect. The power supply effect of the methyl groups (which weakens the tendency of the electron pairs of the CN bond to lean toward the nitrogen atom) weakens the positive charge of the carbon atom, thereby preventing the negatively charged hydroxyl group from attacking the positively charged carbon atom to cause hydrolysis. The prepared fluid loss reducer has no inverted thickening time when the temperature range is between 90°C and 120°C, which fundamentally solves the problem of the inverted thickening time of the fluid loss reducer and eliminates the major engineering safety risks in cementing engineering.
[0016] (2) The present invention utilizes weak polar bonds to connect the temperature-resistant and salt-resistant sulfonic acid groups required for the fluid loss reducer with the main chain. The prepared fluid loss reducer solves the problems of high-temperature chain scission, functional group degradation, high-temperature desorption, and high-temperature dehydration of oil well cement fluid loss reducers under high temperature and alkaline conditions. It not only eliminates the inversion of thickening time caused by hydrolysis of functional groups of the fluid loss reducer, but also solves the problems of uncontrolled water loss in the cement slurry system, reduced gravity stability (cement slurry sedimentation), and the occurrence of "core wrapping", "bulging", "stepping", "super slow setting" and other undesirable phenomena during the thickening process of cement slurry.
[0017] (3) The present invention utilizes the high bond energy of the -CC-σ bond to solve the temperature stability of the main chain of the fluid loss reducer. The fluid loss reducer has strong temperature resistance and can adapt to the cementing slurry system with a circulation temperature of 180°C (equivalent to a formation temperature of 225°C to 230°C).
[0018] (4) The fluid loss reducer prepared by the present invention has a strong ability to control water loss. When the amount of 6.0 to 7.0 is added at a circulation temperature of 180°C (equivalent to a formation temperature of 225°C to 230°C), the water loss can be controlled below 50 mL required by the industry standard for first-class products.
[0019] (5) The fluid loss reducer prepared by the present invention has strong salt resistance, and its salt resistance reaches that of saturated salt water; it can be used in freshwater cement slurry systems of ordinary strata, and can also be applied to salt water cement slurry systems of salt layers and salt water layers.
[0020] (6) The fluid loss reducer prepared by the present invention has good compatibility with other commonly used cement additives and has no adverse effects on the rheology, stability, thickening time, strength and other properties required for cementing engineering of cement slurry; it can be used to prepare cement slurry systems with temperatures of 20°C to 180°C, different densities and different salinities.
[0021] (7) The synthesis method of the present invention is simple and easy to operate, and the raw materials are reasonably priced and readily available, which is convenient for industrial promotion.
[0022] Other advantages, objectives and features of the present invention will be embodied in part through the following description, and in part will be understood by those skilled in the art through study and practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is the infrared spectrum of the fluid loss additive prepared in Example 1.
[0024] Figure 2 This is the HNMR spectrum of the fluid loss additive prepared in Example 1.
[0025] Figure 3 Experiment No. 3-1 # Thickening curve (214min).
[0026] Figure 4 Experiment No. 3-2 # Thickening curve (240min).
[0027] Figure 5 Experiment number 3-3 # Thickening curve (294min).
[0028] Figure 6 Experiment number 3-4 # Thickening curve (319min).
[0029] Figure 7 Experiment number 3-5 # Thickening curve (364min). DETAILED DESCRIPTION
[0030] The preferred embodiments of the present invention are described below in conjunction with the accompanying drawings. It should be understood that the preferred embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0031] Example 1
[0032] A preparation method of a fluid loss agent is as follows:
[0033] (1) Weigh: 46.15 kg of N,N-dimethylacrylamide (DMAM); 20.51 kg of sodium 3-allyloxy-2-hydroxy-1-propanesulfonate (AHPS); 8.21 kg of vinyl pyrrolidone (NVP); and 5.13 kg of sodium methyl allyl sulfonate (MAS).
[0034] (2) Weigh 1.60 kg of initiator sodium persulfate (Na2S2O8); dissolve it in 3.00 kg of water for later use;
[0035] (3) Weigh 0.080 kg of the terminator thiourea [(NH2)2S] and dissolve it in 1.00 kg of water for later use;
[0036] (4) Add 416.0 kg of water into the reactor; add all the four monomers weighed in step (1) into the reactor and stir for 30 minutes to completely dissolve them;
[0037] (5) heating the contents of the reactor to 60°C ± 2°C, and dripping the initiator solution prepared in step (2) into the contents of the reactor over a period of 3 to 5 minutes; keeping the contents of the reactor at 80°C for 6 hours, and when the temperature of the contents of the reactor is too high, starting circulating cooling water to control the reaction temperature;
[0038] (6) After reacting for 6 hours, the terminator thiourea solution prepared in step (3) was added to the reactor at one time to terminate the reaction; and the circulating cooling water was turned on and the temperature was lowered to below 40° C. under stirring to obtain a fluid loss additive product, referred to as fluid loss additive BS100L-ND.
[0039] The oil well cement fluid loss reducer BS100L-ND without inverted thickening time prepared in Example 1 was purified by anhydrous ethanol precipitation-water dissolution-ethanol precipitation three times to remove unreacted monomers and by-products in the system; the precipitate was cut into pieces, dried, and ground; its molecular structure was characterized by infrared spectroscopy and nuclear magnetic hydrogen spectrum. The results are shown in Figure 1 , Figure 2 .
[0040] Figure 1 In the infrared spectrum: 3200cm -1 -3660cm -1 It is the absorption peak of polymer crystal water and the -C-OH stretching vibration absorption peak in AHPS; 2984cm -1 、2929cm -1 The CH stretching vibration peak on the main chain -CH3 and -CH2-; 1664cm -1 is the absorption peak of C=O in DMAM; 1556cm -1 is the absorption peak of C=O in NVP carbonyl; 1468cm -1 The CN stretching vibration peak in DMAM; 1375 cm -1 It is the absorption peak of CH bending vibration on -CH3 and -CH2-; 1203cm -1 is the in-plane bending absorption peak of AHPS monomer -C-OH; 820cm -1 、766cm -1 The bending vibration absorption peak of CH on the long carbon chain skeleton is 1046cm -1 and 633cm -1 The characteristic peaks of the four monomer functional groups all appear in the infrared spectrum, indicating that the polymer is a copolymer of the four monomers.
[0041] Figure 2In the H NMR spectrum: δ = 0.929 is the -C-CH3 chemical shift peak of MAS monomer; δ = 1.429 is the chemical shift peak of C-CH2-C on the main chain; δ = 1.665 is the chemical shift peak of C-CH-C on the main chain; δ = 2.036 is the -CH2-O-CH2 chemical shift peak in AHPS monomer; δ = 2.231 is the C-CH2-C chemical shift peak on the pyrrole ring in NVP monomer; δ = 2.414 is the C-CH2-N chemical shift peak on the pyrrole ring in NVP monomer; δ = 3.290 is N-(CH3)2 in DMAM monomer; δ = 3.782 is -CH2-SO3 in AHPSH and MAS monomers - The chemical shift peak of δ = 3.860 is the chemical shift peak of -CH-OH of AHPS monomer. The H-NMR spectrum analysis shows that it contains all the functional groups of the four monomers DMAM, AHPS, NVP and MAS, indicating that the four monomers are involved in the copolymerization.
[0042] Example 2
[0043] A preparation method of a fluid loss agent is as follows:
[0044] (1) Weigh: 923.1 kg of N,N-dimethylacrylamide (DMAM); 410.2 kg of sodium 3-allyloxy-2-hydroxy-1-propanesulfonate (AHPS); 164.1 kg of vinyl pyrrolidone (NVP); and 102.6 kg of sodium methyl allyl sulfonate (MAS).
[0045] (2) Weigh 32.0 kg of initiator sodium persulfate (Na2S2O8); dissolve it in 60.0 kg of water for later use;
[0046] (3) Weigh 1.60 kg of thiourea [(NH2)2S] as the terminator and dissolve it in 15.0 kg of water for later use;
[0047] (4) Add 8325.0 kg of water into the reactor, add all the four monomers weighed in step (1) into the reactor, and stir for 30 minutes to completely dissolve them;
[0048] (5) heating the contents of the reactor to 60°C ± 2°C, and dripping the initiator solution prepared in step (2) into the contents of the reactor over a period of 3 to 5 minutes; keeping the contents of the reactor at 85°C for 6 hours, and when the temperature of the contents of the reactor is too high, starting circulating cooling water to control the reaction temperature;
[0049] (6) After reacting for 6 hours, add the terminator thiourea solution prepared in step (3) into the reactor at one time to terminate the reaction; and start circulating cooling water, and cool down to below 40° C. under stirring to obtain a fluid loss additive product.
[0050] The performance test of fluid loss additive is as follows:
[0051] The various properties of the cement slurry system were evaluated according to the experimental methods in the industry standard SY / T5504.2-2013 "Evaluation Methods for Oil Well Cement Admixtures Part 2 Fluid Loss Reducers" and the national standard GB / T 19139-2015 "Test Methods for Oil Well Cement". The additives used in the performance evaluation experiment: expansion agent BS500, retarder BS200R-G, flow pattern regulator TC-18, defoamer BP-1, are all produced by Sichuan Hongsheng Petroleum Engineering Technology Service Co., Ltd.
[0052] (1) Inverted performance test evaluation:
[0053] Since the hydrolysis temperature of the fluid loss reducer containing amide bonds is 90-120°C, the thickening time "inverted" phenomenon generally occurs in the cross-temperature zone where the bottom temperature is greater than 120°C and the top temperature is less than 90°C. Under the same formulation, experimental conditions, and fluid loss reducer dosage, the thickening time at 120°C and 75°C was measured. The thickening time inverted rate was calculated using formula (1).
[0054] When D TT When D TT When ≥0, it is determined that there is no inversion in thickening time.
[0055]
[0056] Where:
[0057] D TT75 Represents the inversion rate of thickening time at 75℃, %;
[0058] TT 120 Represents the thickening time at 120°C, min;
[0059] TT 75 Represents the thickening time at 75°C, min.
[0060] Experimental formula and experimental conditions: 600g Jiahua G-grade high sulfur-resistant oil well cement JHG + 40% high temperature stabilizer SiO2 + (5.0-6.0%) fluid loss reducer BS100L-ND + 1.5% retarder BS200R-G + 2.0% flow pattern regulator TC-18 + 0.5% defoamer BP-1 + water, the amount of each substance in the formula is calculated by cement mass (BWOC); the cement slurry density is 1.90g / cm 3 Experimental conditions: heating time 60min, pressure 75MPa. Experiments were conducted at fluid loss agent dosages of 5.0%, 5.5%, and 6.0%, respectively. The experimental results are shown in Table 1.
[0061] Table 1. Experimental data table of evaluation of inverted performance of thickening time of non-inverted fluid loss agent BS100L-ND
[0062]
[0063] The experimental results in Table 1 show that the non-inverted fluid loss reducer BS100L-ND does not have an inverted thickening time. At different fluid loss reducer dosages, the inverted thickening time rate is greater than 0, and the greater the amount of fluid loss reducer, the longer the thickening time. There is no engineering risk, and the inverted thickening time rate is stable. This also shows that the structure and performance of the fluid loss reducer BS100L-ND are stable when it crosses the amide bond hydrolysis sensitive zone of 90℃ to 120℃.
[0064] Comparative Example 1: According to the preparation method of Example 1, DMAM is replaced with an equal amount of AM, and the polymer 1 finally prepared has the following molecular structure:
[0065]
[0066] Comparative Example 2: According to the preparation method of Example 1, the AHPS was replaced with an equal amount of AMPS to finally prepare a polymer 2, the molecular structure of which is as follows:
[0067]
[0068] In comparative example 3, acrylamide (AM), acrylic acid (AA), and sodium 2-acrylamido-2-dimethylpropanesulfonate (AMPS) were used as raw monomers, and polymer 3 was finally prepared according to the same preparation method as in Example 1. The mass ratio of AM, AA, and AMPS was 3:1:5. The amount of initiator was 2.0% of the total mass of the three monomers. The amount of thiourea was 0.1% of the total mass of the three monomers. In the entire reaction system, the mass ratio of water to the total mass of the three monomers was 74:16.
[0069] The molecular structure of polymer 3 is as follows:
[0070]
[0071] According to the same method as above, the inversion performance of the three samples of polymer 1, polymer 2 and polymer 3 were tested respectively.
[0072] Experimental formula and experimental conditions: 600g oil well cement JHG + 40% high temperature stabilizer SiO2 + 5.5% fluid loss reducer + 1.5% retarder BS200R-G + 2.0% flow pattern regulator TC-18 + 0.5% defoamer BP-1 + water, the amount of each substance in the formula is calculated by cement mass (BWOC); the cement slurry density is 1.90g / cm 3Experimental conditions: heating time 60min, pressure 75MPa. The experimental results are shown in Table 2.
[0073] Table 2. Experimental data of evaluation of thickening time inversion performance of polymer 1, polymer 2 and polymer 3
[0074] Polymer Name Addition amount / % <![CDATA[TT 120 / min]]> <![CDATA[TT 75 / min]]> <![CDATA[D TT / %]]> Polymer 1 5.5 327 228 -43.4 Polymer 2 5.5 302 245 -23.3 Polymer 3 5.5 343 204 -68.1
[0075] The experimental results in Table 2 show that after polymer 1 replaces DMAM with AM, its content in the polymer is the largest, the amide hydrolyzability is strong, and after hydrolysis, carboxyl groups with a retarding effect are produced, so the inversion is more serious. After polymer 2 replaces AHPS with AMPS, its sulfonic acid group is connected by an amide bond, and after hydrolysis, carboxyl groups with a retarding effect are produced, and there is also an obvious inversion phenomenon. Polymer 3 contains a large amount of AM and AMPS, and after hydrolysis, a large amount of carboxyl groups with a retarding effect are produced, and the inversion is the most serious. In short, if the polymer contains a carboxyl structure that can be hydrolyzed to produce a retarding effect, the inversion rate of the thickening time is <0, there is an obvious thickening time inversion phenomenon, and the greater the content, the more carboxyl groups are produced, the more serious the inversion, and the higher the engineering risk. Unlike these three fluid loss reducers, the molecular structure of the fluid loss reducer of the present invention has a unique property of preventing the thickening time of cement slurry from being inverted.
[0076] (2) Evaluation of temperature resistance of fluid loss reducer
[0077] Based on the conventional density cement slurry system formula, the water loss control ability of the fluid loss reducer BS100L-ND prepared in Example 1 was evaluated at different temperatures. The experimental results are shown in Table 3.
[0078] Table 3. Conventional density cement slurry system formula and water loss performance experimental data table
[0079]
[0080]
[0081] In Table 3, the expander is expander BS500, and the specific types of other additives are the same as those used in the previous experiments.
[0082] The experimental results in Table 3 show that in a common conventional density cement slurry system, the water loss can be controlled within the range of 120°C to 180°C as required by the first-class product and is within ≤50mL, indicating that the fluid loss reducer of the present invention has excellent temperature resistance.
[0083] (3) Evaluation of salt resistance of fluid loss reducers
[0084] Based on the formula of conventional density cement slurry system, the water loss control ability of fluid loss reducer BS100L-ND was investigated at 150°C and different salinities (NaCl concentrations). The experimental results are shown in Table 4.
[0085] Table 4. Formula and water loss performance of conventional density brine cement slurry system
[0086]
[0087] In Table 4, the specific types of additives such as high temperature stabilizers, retarders, expanders, flow pattern regulators, defoamers, etc. are the same as those used in the previous experiments.
[0088] The experimental results in Table 4 show that: with the increase of salt concentration, the water loss of the cement slurry system increases slightly. In the high concentration or saturated salt water system, only a small amount of fluid loss reducer is needed to ensure that the water loss is controlled within the requirement of 50 mL, which shows that the fluid loss reducer of the present invention has excellent salt resistance.
[0089] (4) Comprehensive performance evaluation of fluid loss additives
[0090] In actual cementing projects, each well faces different engineering conditions and requirements, requiring cement slurry systems with different properties, such as different densities, different temperatures, etc. Different cement slurry systems were prepared with the fluid loss reducer BS100L-ND prepared in Example 1, and the comprehensive engineering performance of the fluid loss reducer at conventional density was investigated in the range of 75°C to 180°C. The experimental formula is shown in Table 5, the experimental test data is shown in Table 6, and the thickening curve of the experimental sample is shown in Table 7. Figure 3-7 .
[0091] Table 5. Conventional density cement slurry system formula and water loss performance experimental data table
[0092]
[0093] In the table, the specific types of additives such as high temperature stabilizers, retarders, expanders, flow pattern regulators, defoamers, etc. are the same as those used in the previous experiments.
[0094] Table 6. Experimental data of comprehensive engineering performance of conventional density cement slurry system
[0095]
[0096] Table 5, Table 6 and Figure 3-7 The experimental results show that the fluid loss reducer of the present invention can be formulated into a cement slurry system for cementing at 75°C to 180°C with a conventional density by properly mixing the fluid loss reducer and the amount of the retarder and adding the expansion agent, the flow pattern regulator and the defoaming agent. The engineering performance indicators of the cement slurry system such as water loss, rheology, free liquid, thickening time, compressive strength, and gravity stability meet the requirements of industry standards.
[0097] The above description is only a preferred embodiment of the present invention and does not constitute any form of limitation to the present invention. Although the present invention has been disclosed as a preferred embodiment as above, it is not intended to limit the present invention. Any technician familiar with the profession can make some changes or modifications to equivalent embodiments of equivalent changes using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the scope of the technical solution of the present invention.
Claims
1. A fluid loss reducer for oil well cement without inverted thickening time, characterized in that: It is prepared by copolymerizing four raw material monomers, namely, N,N-dimethylacrylamide, 3-allyloxy-2-hydroxy-1-1 propane sulfonate sodium, vinyl pyrrolidone, and methyl allyl sulfonate sodium, in a mass ratio of (44-46): (18-21): (6-9): (4-7); the molecular structure of the fluid loss reducer is as follows:
2. A method for preparing the oil well cement fluid loss reducer with no inverted thickening time as claimed in claim 1, characterized in that: The following steps are involved: S1, adding four raw material monomers, namely, N,N-dimethylacrylamide, 3-allyloxy-2-hydroxy-1-1-propanesulfonic acid sodium, vinyl pyrrolidone, and methyl allyl sulfonic acid sodium, into water, stirring and dissolving to obtain a reaction solution; S2. Raise the temperature of the reaction solution to 60°C ± 2°C, add the initiator solution dropwise within 3 to 5 minutes, and then keep the temperature at 80°C to 85°C for 6 hours; S3. After the reaction time reaches 6 hours, add the terminator thiourea solution to terminate the reaction; and start the circulating cooling water, and cool down to below 40°C while stirring. The obtained solution is the fluid loss reducer.
3. The method for preparing the oil well cement fluid loss reducer without inverted thickening time as claimed in claim 2, characterized in that: The initiator is sodium persulfate, and the amount of the initiator used is 2.0% of the total mass of the four monomers, and is dissolved in water to form an initiator solution.
4. The method for preparing the oil well cement fluid loss reducer without inverted thickening time as claimed in claim 2, characterized in that: In step S2, during the reaction process, the reaction temperature is controlled not to exceed 85° C. by circulating cooling water.
5. The method for preparing the oil well cement fluid loss reducer without inverted thickening time as claimed in claim 2, characterized in that: The thiourea solution is a solution formed by dissolving thiourea in water, and the amount of thiourea used is 0.1% of the total mass of the four monomers.
6. The method for preparing the oil well cement fluid loss reducer without inverted thickening time as claimed in claim 2, characterized in that: In the entire reaction system, the mass ratio of water to the total mass of the four monomers is 74:16.
Citation Information
Patent Citations
High-temperature-resistant dispersed fluid loss agent for oil well cement and preparation method thereof
CN102191027A
High-temperature-resistant salt-resistant water loss reducer and preparation method and application thereof
CN108929405A
Water loss reducing agent with thickening and inverting prevention performance, preparation method and application of agent
CN110054730A
Oil well cement fluid loss agent for solving problem of thickening and core wrapping of cement paste and preparation method thereof
CN111153624A
Novel drag reducer for oil well cement, and preparation method thereof
CN111218263A